The Impact of Sibling Rivalry on the 5 to 6 Years Old Children’s Characters - Jatmiko, Agus; Mulya, Neni (Universitas Islam Negeri Raden Intan Lampung, 2023)
The presence of siblings in a child's life brings changes that require the child to share in various things, including parental love. It gives rise to a competitive rivalry between siblings in feelings or actions. This research aims to determine the impact of sibling rivalry (fights between siblings), which affects the character development of children aged 5-6 years. The method employed in this research is a qualitative case study. The data-collecting techniques employed were interviews, observation, and documentation. Based on the analysis, sibling rivalry has several impacts on children aged 5-6 years, namely the impact on oneself or regression, the impact on siblings or aggression, and the impact on others or bad behaviour directed at people outside of the home. Sibling rivalry is also caused by bad relationships, parenting patterns, and the environment, which can increase the impact on children.